A study of clinical course and therapeutic response of sexually transmitted infections in people living with HIV/AIDS - Halder, Ram Kanta; Balasubramanian, Pradeep (International Journal of Research in Dermatology, 2019)
Background: Human immunodeficiency virus (HIV) continues to be a major public health problem worldwide. Once a person is infected with HIV, the manifestations of other infections and diseases are altered due to waning of the host immunity. Methods: This study was carried out in HIV reactive patients in Command Hospital, Pune. The types of sexually transmitted infections (STIs) in those patients and the response to therapy were studied in detail. The statistical data was expressed as number and percentages. Results: In this study, 52 people living with HIV/AIDS (PLWHA) who were having various STIs were included. Majority of the patients in this study belonged to the age group of 20-34 years (75%). The most common STIs encountered were condyloma acuminata (38.45%) followed by syphilis (30.77%), lymphogranuloma venereum, herpes genitalis, chancroid, molluscum contagiosum, gonorrhea and granuloma inguinale. Resistance to antimicrobial therapy at the standard dosage, requirement of higher dosage, resistance and relapse of infections were observed in the patients with PLWH. Conclusions: Several STIs coexisted with HIV infected patients. Unusual clinical presentations, clinical course and treatment failure in STI were common in HIV infected individuals. Hence all STI patients should be screened for HIV and vice-versa.